KAJIAN KOMUNIKASI LEGISLATIF DAN EKSEKUTIF DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN YANG BAIK DI KABUPATEN KONAWE SELATAN - Asriani, Asriani; Alam, Syamsul; Dasmin, Dasmin; Elfrianto, La Ode (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
South Konawe Regency, the executive and legislature as regional government partners are continuously involved in communication about how to manage and allocate public resources, official authority, official sanctions and other political actions. In various situations, both parties communicate in formal or informal forms. The aim of this research is to describe and analyze forms of communication, the dominant political communication culture, and the basic obstacles that limit legislative and executive opportunities to communicate more effectively in realizing good governance in South Konawe Regency. This research uses a qualitative approach. The data collection techniques that will be used are Desk Study and Interview. Research informants were determined purposively. The interactive analysis method according to Miles and Huberman, namely the stages of data collection, reduction, data presentation and drawing conclusions, was used in this research. The research results show that the forms of communication that exist between the Legislative (DPRD) and the Executive (PEMDA) of South Konawe Regency are formal communication and informal communication. Formal communication is realized in harmony between the two institutions in carrying out their respective functions. As for informal forms of communication, when there is a problem that is difficult and cannot be resolved in formal communication, informal channels are a solution so that the relationship between the two remains in harmony and continues to go hand in hand. The political culture that is built and attached to political elites, both legislative and executive, is a political communication culture that upholds family values. This cultural approach to political communication has proven effective in breaking the ice. This cultural closeness is a sign that political actors continue to maintain. Bearing in mind that this area is known as a miniature Indonesia with a diversity of ethnic, religious and racial identities, which makes family relations a close bond between one another. Barriers to organizational communication that occur within regional government and DPRD are technical barriers; digital infrastructure in providing adequate internet access and fast response in communication via WhatsApp social media as a communication medium in the digital era. Technical obstacles that cause communication channels to not run effectively or not be used properly, because technical matters certainly affect operational performance. Semantic barriers; clarity of communication (clarity) which is related to the presence of unclear or one-sided information that gives rise to differences in views.